Validation of the systemic lupus erythematosus responder index for use in juvenile-onset systemic lupus erythematosus. Issue 2 (23rd January 2013) - Mina, Rina; Klein-Gitelman, Marisa S; Nelson, Shannen; Eberhard, B Anne; Higgins, Gloria; Singer, Nora G; Onel, Karen; Tucker, Lori; O'Neil, Kathleen M; Punaro, Marilynn; Levy, Deborah M; Haines, Kathleen; et al.
Abstract : Objectives: This study tested the concurrent validity of the systemic lupus erythematosus responder index (SRI) in assessing improvement in juvenile-onset systemic lupus erythematosus (jSLE). Methods: The SRI considers changes in the SELENA–SLEDAI, BILAG and a 3-cm visual analogue scale of physician-rated disease activity (PGA) to determine patient improvement. Using prospectively collected data from 760 unique follow-up visit intervals of 274 jSLE patients, we assessed the sensitivity and specificity of the SRI using these external standards: physician-rated improvement (MD-change), patient/parent-rated major improvement of wellbeing (patient-change) and decrease in prescribed systemic corticosteroids (steroid-change). Modifications of the SRI that considered different thresholds for the SELENA–SLEDAI, BILAG and 10-cm PGA were explored and agreement with the American College of Rheumatology/PRINTO provisional criteria for improvement of jSLE (PCI) was examined. Results: The sensitivity/specificity in capturing major improvement by the MD-change were 78%/76% for the SRI and 83%/78% for the PCI, respectively. There was fair agreement between the SRI and PCI (kappa=0.35, 95% CI 0.02 to 0.73) in capturing major improvement by the MD-change. Select modified versions of the SRI had improved accuracy overall. All improvement criteria tested had lower sensitivity when considering patient-change and steroid-change as external standards compared to MD-change. Conclusions: The SRI and its modified versions based on meaningful changes in jSLE have high specificity but at most modest sensitivity for capturing jSLE improvement. When used as an endpoint of clinical trials in jSLE, the SRI will provide a conservative estimate regarding the efficacy of the therapeutic agent under investigation.